Usefulness of the polymerase chain reaction dot-blot assay, used with Ziehl-Neelsen staining, for the rapid and convenient diagnosis of pulmonary tuberculosis in human immunodeficiency virus-seropositive and -seronegative individuals - Luciene Cardoso Scherer; Rosa D. Sperhacke; Maria L. R. Rossetti; Antonio Ruffino-Netto; Afrânio L. Kritski (MDPI AG, 2011)
There are scarce data regarding the value of molecular tests, when used in parallel with classical tools, for the diagnosis of tuberculosis (TB) under field conditions, especially in regions with a high burden of TB-human immunodeficiency virus (HIV) co-infection. We evaluated the usefulness of the polymerase chain reaction dot-blot assay (PCR) used in parallel with Ziehl-Neelsen staining (ZN) for pulmonary tuberculosis (PTB) diagnosis, in a TB-HIV reference hospital. All sputum samples from 277 patients were tested by ZN, culture, and PCR. Performances were assessed individually, in parallel, for HIV status, history of anti-TB treatment, and in different simulated TB prevalence rates. Overall, the PTB prevalence was 46% (128/277); in HIV-seropositive (HIV+) individuals, PTB prevalence was 54% (40/74); the ZN technique had a lower sensitivity (SE) in the HIV+ group than in the HIV-seronegative (HIV-) group (43% vs. 68%; Fisher test, P<0.05); and the SE of PCR was not affected by HIV status (Fisher test; P=0.46). ZN, in parallel with PCR, presented the following results: i) among all PTB suspects, SE of 90%, specificity (SP) of 84%, likelihood ratio (LR)+ of 5.65 and LR- of 0.12; ii) in HIV- subjects: SE of 92%, LR- of 0.10; iii) in not previously treated cases: SE of 90%, LR- of 0.11; iv) in TB, prevalence rates of 5-20%; negative predictive values (NPV) of 98-99%. ZN used in parallel with PCR showed an improvement in SE, LR-, and NPV, and may offer a novel approach in ruling out PTB cases, especially in not previously treated HIV- individuals, attended in hospitals in developing nations.